Microlicia ferricola (Lavoisiereae), a new species of Melastomataceae from the Iron Quadrangle, Minas Gerais, Brazil - Versiane, Ana Flávia Alves; Rocha, Maria José Reis Da; Santos, Amanda Alves; Romero, Rosana (Phytotaxa, 2024)
Here, we describe Microlicia ferricola, a newly discovered species exclusive to the Iron Quadrangle, Minas Gerais state. Additionally, we provide an illustration plate, field images, occurrence map, and comparisons with its morphological relatives such as M. longicalycina, M. woodgyeriana, and M. trichocalycina. This new species is characterized by its green-reddish to reddish branches, leaves, hypanthia, and sepals covered with glandular trichomes, lanceolate to elliptic-lanceolate leaves, setose at the apices, campanulate-oblong hypanthia, long-triangular sepals, dimorphic and bicolorous androecium with tetrasporangiate anthers. Microlicia ferricola is found in the Serra do Rola-Moça State Park and is considered a Least Concern (LC) taxon since it is within a conservation unit, ensuring its preservation.